Comparative genomics analysis of Stenotrophomonas maltophilia strains from a community - Li, Yini; Liu, Xin; Chen, Lingzhi; Shen, Xiao; Wang, Haihong; Guo, Ruiyu; Li, Xiang; Yu, Zehui; Zhang, Xiaoli; Zhou, Yingshun; Fu, Li (Frontiers in Cellular and Infection Microbiology, 2023)
Background Stenotrophomonas maltophilia is a multidrug-resistant (MDR) opportunistic pathogen with high resistance to most clinically used antimicrobials. The dissemination of MDR S. maltophilia and the difficult treatment of its infection in clinical settings are global issues.To provide more genetic information on S. maltophilia and find a better treatment strategy, we isolated five S. maltophilia, SMYN41-SMYN45, from the community in China which were subjected to antibiotic susceptibility testing, biofilm formation assay, and whole-genome sequencing. The whole genome sequences were compared with other thirty-seven S. maltophilia sequences.Results These five S. maltophilia strains had similar antibiotic resistance profiles that were resistant to β-lactams, aminoglycosides, and macrolides. They showed similar antimicrobial resistance (AMR) genes, including various efflux pumps, β-lactamase resistant genes (blaL1/2), aminoglycosides resistant genes [aac(6'), aph(3'/6)], and macrolide resistant gene (MacB).Genome sequencing analysis revealed that SMYN41-SMYN45 belonged to sequence type 925 (ST925), ST926, ST926, ST31, and ST928, separately, and three new STs were identified (ST925, ST926 and ST928).Conclusions This study provides genetic information by making a comparison of genome sequences of several S. maltophilia isolates from a community and various origins, expecting to optimize empirical medication of antibiotics and contributing to the worldwide efforts of tackling antibiotic resistance.